(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Today’s article talks about the economic relations arising from the creation, accumulation, distribution and redistribution or use of centralized and decentralized monetary funds. Finance occurs in the monetary sector of the economy and is noted to occur on the basis of income